Synthesis and Investigation into Apatite-forming Ability of Hydroxyapatite/Chitosan-based Scaffold - Thanh Hoai, Tran; Kim Nga, Nguyen (VNU Journal of Science: Natural Sciences and Technology, 2019)
In this study, porous scaffolds were fabricated using inorganic material-hydroxyapatite and chitosan for bone-tissue engineering. The combination of hydroxyapatite and chitosan may result in increasing biocompatibility of the scaffolds. The scaffolds were prepared by solvent casting and paticulate leaching method. Bioactivity of the scaffolds was evaluated through in vitro experiments by soaking scaffold samples in simulated body fluid (SBF). The scaffolds obtained were highly porous and interconnected with a mean pore size of around 200µm and porosity about 79 %. The apatite-mineral layer was produced on the HAp/chitosan after 10 days of soaking in SBF, however, it was not observed on the chitosan scaffold after 10 days soaking. The results revealed that the HAp/chitosan scaffold showed better bioactivity than the chitosan scaffold. Keywords Scaffold, Chitosan, Apatite, SBF. In this study, porous scaffolds were fabricated using inorganic material-hydroxyapatite and chitosan for bone-tissue engineering. The combination of hydroxyapatite and chitosan may result in increasing biocompatibility of the scaffolds. The scaffolds were prepared by solvent casting and paticulate leaching method. Bioactivity of the scaffolds was evaluated through in vitro experiments by soaking scaffold samples in simulated body fluid (SBF). The scaffolds obtained were highly porous and interconnected with a mean pore size of around 200µm and porosity about 79 %. The apatite-mineral layer was produced on the HAp/chitosan after 10 days of soaking in SBF, however, it was not observed on the chitosan scaffold after 10 days soaking. The results revealed that the HAp/chitosan scaffold showed better bioactivity than the chitosan scaffold. Keywords: Scaffold, Chitosan, Apatite, SBF.   In this study, porous scaffolds were fabricated using inorganic material-hydroxyapatite and chitosan for bone-tissue engineering. The combination of hydroxyapatite and chitosan may result in increasing biocompatibility of the scaffolds. The scaffolds were prepared by solvent casting and paticulate leaching method. Bioactivity of the scaffolds was evaluated through in vitro experiments by soaking scaffold samples in simulated body fluid (SBF). The scaffolds obtained were highly porous and interconnected with a mean pore size of around 200µm and porosity about 79 %. The apatite-mineral layer was produced on the HAp/chitosan after 10 days of soaking in SBF, however, it was not observed on the chitosan scaffold after 10 days soaking. The results revealed that the HAp/chitosan scaffold showed better bioactivity than the chitosan scaffold. Keywords: Scaffold, Chitosan, Apatite, SBF. References [1] M.P. Bostrom, D.A. Seigerman, The clinical use of allografts, demineralized bone matrices, synthetic bone graft substitutes and osteoinductive growth factors: a survey study, Hss. Journal 1 (2005) 9-18. https://doi.org/10. 1007/s11420-005-0111-5. [2] T.T. Hoai, N.K Nga, L.T. Giang, T.Q. Huy, P.N.M. Tuan, B.T.T. Binh, Hydrothermal Synthesis of Hydroxyapatite Nanorods for Rapid Formation of Bone-Like Mineralization, J. Electron. Mater. 46 (2017) 5064-5072. https:// doi.org/10.1007/s11664-017-5509-6. [3] M. Rinaudo, Chitin and chitosan: properties and applications, Prog. Polym. Sci. 31 (2006) 603-632. https://doi.org/10.1016/j.progpolymsci.2006. 06.001. [4] N.K. Nga, H.D. Chinh, P.T.T Hong, T.Q. Huy, Facile chitosan films for high performance removal of reactive blue 19 dye from aqueous solution, J. Polym. Environ. 25 (2007) 146-155. https://doi.org/10.1007/s10924-016-0792-5. [5] M.N.V Ravi Kumar, R.A.A Muzzarelli, H. Sashiwa, A.J. Domb, Chitosan chemistry and pharmaceutical perspectives, Chem. Rev. 104 (2004) 6017-6084. https://doi.org/10.1021/cr03 0441b. [6] J.M. Karp, M.S. Shoichet, J.E. Davies, Bone formation on two‐dimensional poly (DL‐lactide‐co‐glycolide)(PLGA) films and three‐dimensional PLGA tissue engineering scaffolds in vitro, J. Biomed. Mater. Res. A 64 (2003) 388-396. https://doi.org/10.1002/jbm.a.10420. [7] J.F. Mano, R.L. Reis, Osteochondral defects: present situation and tissue engineering approaches, J. Tissue. Eng. Regen. Med. 1 (2007) 261-273. https://doi.org/10.1002/term.37. [8] A.G. Mikos, J.S. Temenoff, Formation of highly porous biodegradable scaffolds for tissue engineering, Electron. J. Biotechn. 3 (2000) 23-24. http://dx.doi.org/10.4067/S0717-3458200000 0200003. [9] W.W. Thein-Han, R.D.K Misra, Biomimetic chitosan–nanohydroxyapatite composite scaffolds for bone tissue engineering, Acta Biomater. 5 (2009) 1182–1197. https://doi.org/ 10.1016/j.actbio.2008.11.025. [10] Y. Zhang, J.R. Venugopal, A.E. Turki, S. Ramakrishna, B. Su, C.T. Lim, Electrospun biomimetic nanocomposite nanofibers of hydroxyapatite/chitosan for bone tissue engineering, Biomaterials 29 (2008) 4314–4322. https://doi.org/10.1016/j.biomaterials.2008.07.038. [11] B.X. Vương, Tổng hợp và đặc trưng vật liệu composite hydroxyapatite/chitosan ứng dụng trong kỹ thuật y sinh.,Tạp chí Khoa học ĐHQGHN: Khoa học Tự nhiên và Công nghệ Tập 34 (2018) 9-15. https://doi.org/10.25073/ 2588-1140/vnunst.4689. [12] N.K. Nga, T.T. Hoai, P.H. Viet, Biomimetic scaffolds based on hydroxyapatite nanorod/poly (D, L) lactic acid with their corresponding apatite-forming capability and biocompatibility for bone-tissue engineering, Colloids Surf. B Biointerf. 128 (2015) 506-514. https://doi.org/10. 1016/j.colsurfb.2015.03.001. [13] N.K. Nga, L.T. Giang, T.Q. Huy, C. Migliaresi, Surfactant-assisted size control of hydroxyapatite nanorods for bone tissue engineering, Colloids Surf. B: Biointerf. 116 (2014) 666-673. https://doi.org/10.1016/j.colsurfb.2013.11.001. [14] C.R. Kothapalli, M.T. Shaw, M. Wei, Biodegradable HA-PLA 3-D porous scaffolds: effect of nano-sized filler content on scaffold properties, Acta Biomater. 1 (2005) 653-662. https://doi.org/10.1016/j.actbio.2005.06.005. [15] T. Kokubo, H. Takadama, How useful is SBF in predicting in vivo bone bioactivity?, Biomaterials 27 (2006) 2907-2915. https://doi.org/10.1016/j. biomaterials.2006.01.017 [16] T.T. Hoai, N.K. Nga, Effect of pore architecture on osteoblast adhesion and proliferation on hydroxyapatite/poly (D, L) lactic acid-based bone scaffolds, J. Iran. Chem. Soc. 15 (2018) 1663-1671. https://doi.org/10.1007/s13738-018-1365-4.